2021
DOI: 10.3389/fpubh.2020.559693
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling Predicts That Strict Social Distancing Measures Would Be Needed to Shorten the Duration of Waves of COVID-19 Infections in Vietnam

Abstract: Coronavirus disease 2019 (COVID-19) emerged in Wuhan, China in 2019, has spread throughout the world and has since then been declared a pandemic. As a result, COVID-19 has caused a major threat to global public health. In this paper, we use mathematical modeling to analyze the reported data of COVID-19 cases in Vietnam and study the impact of non-pharmaceutical interventions. To achieve this, two models are used to describe the transmission dynamics of COVID-19. The first model belongs to the susceptible-expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Social distancing is one of the impactful disease prevention practices during any airborne disease outbreak [68] , [69] , [70] . In the absence of effective vaccines and therapeutics, this strategy can impede disease transmission and thus can provide some precious time for reallocating and optimizing medical resources [71] . Recent works enlighten us about the effectiveness of social distancing amid the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Social distancing is one of the impactful disease prevention practices during any airborne disease outbreak [68] , [69] , [70] . In the absence of effective vaccines and therapeutics, this strategy can impede disease transmission and thus can provide some precious time for reallocating and optimizing medical resources [71] . Recent works enlighten us about the effectiveness of social distancing amid the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we model the transport and diffusion of the virus in the air following a cough or sneeze of an infectious individual. We consider that whenever an individual coughs or sneezes, they produce a concentration of the virus between 277 × 10 −6 copies/cm 3 and 36,030 copies/cm 3 [58][59][60], depending on their viral load, and within a diameter of d 0 = 1 m. Then, the concentration of viral particles is spread to the computational mesh using a radial-basis function [19][20][21]:…”
Section: Modeling Virus Diffusion and Disease Transmission 231 Virus ...mentioning
confidence: 99%
“…Indeed, a social force model was applied to quantify the impact of non-pharmaceutical interventions on indoor disease transmission [18]. We have previously used a social force model to develop a multi-scale framework that describes COVID-19 transmission dynamics [19][20][21]. This framework describes transmission through respiratory droplets and contamination by infected surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…As we noted above, the traditional compartmental model with constant transition rates allowing to simulate only one peak in the spread of infection, so many authors use various techniques to account for changes in model parameters over time. Bouchnita et al (2021) adapted SEIR model to review the restrictions introduced by Vietnamese government to stop the first wave of COVID-19 pandemic. Authors divided the observed timespan into two periods.…”
Section: Related Researchmentioning
confidence: 99%